2019
DOI: 10.1038/s41598-019-55177-9
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional correlates of the pathological phenotype in a Huntington’s disease mouse model

Abstract: Huntington disease (HD) is a fatal neurodegenerative disorder without a cure that is caused by an aberrant expansion of CAG repeats in exon 1 of the huntingtin (HTT) gene. Although a negative correlation between the number of CAG repeats and the age of disease onset is established, additional factors may contribute to the high heterogeneity of the complex manifestation of symptoms among patients. This variability is also observed in mouse models, even under controlled genetic and environmental conditions. To b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 60 publications
4
17
0
Order By: Relevance
“…Nfib is involved in forebrain development and is essential during embryogenesis (Steele-Perkins et al 2005). Slit1 is involved in cell migration and axonal guidance and its up-regulation was previously associated with “poor” behavior and a worse prognosis in the R6/1 mouse model (Gallardo-Orihuela et al 2019). Ncald is involved in the regulation of G protein-coupled receptor signal transduction and is also implicated in the regulation of multiple endocytosis-dependent neuronal functions, synaptic vesicle recycling, and neurotransmitter release (Vercauteren et al 2007, Yamatani et al 2010, Riessland et al 2017).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nfib is involved in forebrain development and is essential during embryogenesis (Steele-Perkins et al 2005). Slit1 is involved in cell migration and axonal guidance and its up-regulation was previously associated with “poor” behavior and a worse prognosis in the R6/1 mouse model (Gallardo-Orihuela et al 2019). Ncald is involved in the regulation of G protein-coupled receptor signal transduction and is also implicated in the regulation of multiple endocytosis-dependent neuronal functions, synaptic vesicle recycling, and neurotransmitter release (Vercauteren et al 2007, Yamatani et al 2010, Riessland et al 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Connectivity analyses (showing only 15% of the most highly connected members of the Greenyellow module) ( Fig. 6E ) revealed that the two most connected genes within the hub were Slit1 (Slit Guidance Ligand 1), associated with “poor” behavior and a worse prognosis in the R6/1 mouse mode (51), and Ncald (Neurocalcin delta), which regulates multiple endocytosis-dependent neuronal functions and is situated on a locus that has been associated with earlier clinical onset of HD (52, 53) . To better understand which specific genes were more impacted in their expression by CK2α’ depletion, we examined the Differential Gene Expression (DGE) between control mice (WT and CK2α’ (+/-) ) and HD mice (zQ175 and zQ175:CK2α’ (+/-) ) ( Table S3 ).…”
Section: Resultsmentioning
confidence: 99%
“…To date, there have been multiple studies evaluating molecular and cellular mechanisms of abnormal development in HD. For example see recent studies on transcriptomics [ 4 ], and studies of induced pluripotent stem cell lines [ 5–12 ], as well as studies investigating abnormal brain development in HD animal models [ 13–17 ]. As a whole, this literature is rich and supports the notion that abnormal development may play a role in the pathogenesis of disease.…”
mentioning
confidence: 99%
“…Aberrant transcriptional regulation in brain, especially in striatum and cortex, is an early and central feature of HD pathogenesis in models and patients. In the R6/1 model, consistent transcriptional dysregulation in the brain was shown starting with the earliest microarray reports ( Kuhn et al, 2007 ; Benn et al, 2010 ) and more recently by RNA-sequencing studies ( Gallardo-Orihuela et al, 2019 ; Yildirim et al, 2019 ). Among the genes with aberrant expression in HD striatum are transcriptional regulators (e.g., Fos , Egr1 , Npas4 , and Polr2a ) as well as key neuronal genes important for neurotransmitter signaling (e.g., Drd1 , Drd2 , Grin3a , and Ppp1r1b ) and synaptic plasticity (e.g., Arc and Syp ) ( Seredenina and Luthi-Carter, 2012 ; Vashishtha et al, 2013 ; Yildirim et al, 2019 ).…”
Section: Resultsmentioning
confidence: 73%